PENGARUH METODE MUROJA’AH TERHADAP KEMAMPUAN MENGHAFAL AL-QUR’AN JUZ 30 SISWA KELAS V MI AL HIJRAH 01 NGAWI - Imam Wahyudi; Uswatun hasanah (Kurikula : Jurnal Pendidikan, 2022)
Rapid technological advances make parents worry about their children's personal and education. The existence of Al-Qur'an memorization activities at Madrasah Ibtidaiyah can solve the problems that exist in society, causing the children's motivation, interest in learning, memorization ability, learning achievement, and Ubudiyah to decrease. The method used is Muroja'ah, the Muroja'ah method is very effective in the Tahfidzul Qur'an program. The research method used in this study is a quantitative method, with a pre-experimental approach or initial experiment. Data collection techniques in the form of oral exams that have been tested and analyzed using validity and reliability. The results obtained from SPSS 22 have a significant positive effect on the ability to memorize chapter 30. Initial data analysis used normality tests, homogeneity tests, and hypothesis testing using one-way ANOVA. The results of data analysis can be concluded that there is a significant effect between the Muroja'ah method on increasing the ability to memorize chapter 30, based on the results of the interpretation of the ANOVA hypothesis, the value is 0.018 0.05 with a percentage increase of 27% on the results of the Pots-test on the Muroja' method. ah, so that Ho is rejected and Ha is accepted, it is concluded that there is an influence of the Muroja'ah method. Keywords: Muroja’ah method, Memorization ability, ANOVA